PENDIDIKAN KESEHATAN AUDIO VISUAL SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN IBU TENTANG PERTOLONGAN PERTAMA CHOKING PADA ANAK TODDLER - Cholilatul Kamila; Baitus Sholehah; S. Tauriana (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Choking is a common emergency situation for toddlers and can lead to death if not treated quickly and appropriately. Poor knowledge of early childhood mothers in providing first aid is a major risk factor in handling choking. Objective: This study aims to determine the effect of health education using audiovisual media on improving early childhood mothers' knowledge in handling choking in toddlers. Methods: The research method used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 90 early childhood mothers with toddler-aged children. The intervention consisted of providing audiovisual educational videos for one week. Knowledge was measured before and after the intervention using a questionnaire. Data analysis used the Wilcoxon test. Results: The results showed a significant increase in maternal knowledge after receiving health education through audiovisual media with a significance value of p = 0.000. Conclusion: The conclusion is that health education using audiovisual media is effective in improving early childhood mothers' knowledge in handling choking in toddlers. Audiovisual media provides a more engaging, interactive, and easy-to-understand learning approach, making it an effective alternative for health education in the community.